When Confirmation Bias Outweighs Expertise: A Factorial Survey On Credibility Judgments Of Polarizing Covid-19 News - Sandra Walzenbach; Thomas Hinz (ZBW - Leibniz Information Centre for Economics, 2025)
In today's digital media landscape, individuals must judge the credibility of competing information from an unprecedented range of sources, including established news organizations, political actors, unverified online voices and self-declared experts. Building on a theoretical discussion of how the internet and social media – with its algorithmic curation, its omnipresent misinformation and strategic disinformation – have altered media consumption, this study examines the challenges individuals face in evaluating the credibility of media content. Informed by dual-process theory and the concept of motivated reasoning, we explore the roles of both belief-consistency and established quality cues (namely source expertise and data references) in shaping credibility judgments. We use the Covid-19 pandemic in Germany as a case study of polarization, contrasting an inconspicuous majority with a vocal minority represented by the “Querdenker” protest movement. Heavily relying on social media, this movement mobilized a heterogeneous base of supporters united by deep-rooted mistrust of politics, science, and mainstream media. To investigate these dynamics, we conducted a factorial survey experiment in which a general population sample evaluated the credibility of Covid-19–related media content. The results provide strong evidence of confirmation bias, no detectable effect of quality cues, and remarkably similar evaluation strategies across both groups.
Keywords: 300; public opinion; media perception; polarization; Covid-19; confirmation bias; factorial survey experiment